Effect of Eight Weeks Sports Programs on Blood Irisin Level in Healthy Male Sport Practitioners - Al-Naemi, Raed; Khalid, Azad; Al-Doski, Dilshad (Humanities Journal of University of Zakho, 2021)
The main aim of this study is to assess the effect of three different types of exercises on Irisin hormone level, body fat, visceral fat, BMI and lipid profile in sports practitioners. The experimental approach was used to conduct the study. A 66 healthy male sport practitioners were participated in this study and divided into three experimental groups, each group consist of 22 subjects, the first group performed aerobic exercises (AE), the second group performed anaerobic exercises (AnE), and the third group, performed resistance exercises (RE). Before entering their experimental program, the three groups conducted the beep test for determining the VO2max for each participant, and then the blood samples were taken from each participant. Thereafter, the three groups entered the training program for eight weeks 3 times/week. After ending the training programs, the three groups conducted the beep test again for determining the VO2max, and the blood samples were taken from the participants. All statistical data analyses were performed using SPSS version 25. For checking the differences between the pre-test for all groups one-way ANOVA with Post Hok-Tukey was conducted, and the same for the post-test variables. Comparisons between pre-test and post-test within one type of exercise were performed by the paired sample t-test. The three types of exercise for the sport practitioners after participating in intervention for 8 weeks’ program were effective. Interestingly, the sport exercises were found to have a great effect on increasing Irisin serum level and decrease the bod fat, visceral fat and BMI following the three type of exercise. It was found that resistance exercises are more effective to increase the level of Irisin hormone than aerobic and anaerobic exercises.